Republic of Latvia : Ex Post Evaluation of Exceptional Access Under the 2008 Stand-By Arrangement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Latvia. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2013)
The IMF has approved an exceptional access Stand-By Arrangement for Latvia. The program is part of a coordinated international effort that has improved financial and economic stability. By early 2008, the fast growth has leveled off but severe vulnerabilities turned the slowdown into a crisis. Immediate steps to stabilize the financial sector and help stem reserve losses has focused on resolving the systemic Parex Bank, which is experiencing a deposit run. Measures to ensure long-term external viability has focused on fiscal and income policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet